Plastic repair: A basic guide to identifying thermoplastic and thermoset components - FOS (John Deere, 1994)
This book describes approved methods of repairing plastic parts. shows how to identify different types of plastics with special tests to explaining how to repair the particular damaged plastic. This book is filled with illustrations to clearly demonstrate what must be done.. phothgraphs, drawings, pictorial diagrams, tables, and charts